If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x = (33x + -14) Reorder the terms: 13x = (-14 + 33x) Remove parenthesis around (-14 + 33x) 13x = -14 + 33x Solving 13x = -14 + 33x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-33x' to each side of the equation. 13x + -33x = -14 + 33x + -33x Combine like terms: 13x + -33x = -20x -20x = -14 + 33x + -33x Combine like terms: 33x + -33x = 0 -20x = -14 + 0 -20x = -14 Divide each side by '-20'. x = 0.7 Simplifying x = 0.7
| 2+9y-65x=345 | | 5a-7=3a-1 | | 82-6x=12x+22 | | 9-10x=169-45x | | (-3y-6z)(-9)= | | 43-6x=12x+19 | | 7-7x=107-42x | | 0.5b-10=24 | | 3(2x+5)=2(2-x) | | 8x-5=91 | | 0.6x^2+3.6x+3=0 | | m^3-6m^2+8m-7=0 | | m^4-6m^2+8m-7=0 | | 2+=a | | 7(2x-1)=x+3 | | 7(x-1)=x+3 | | -5=-5x | | 2x^4+x^3-3x^2+x+2=0 | | 9-3(x-1)=2x | | 4(2x-1)=x+3 | | X=2.5 | | -x^2-1+2m=0 | | 21-2x=5x-10.5 | | 4x+3+5x=6 | | 115-2x=16x+23 | | -25=5(1-2x) | | x-1=3x+3 | | x-15=-20 | | x^3+8x^2+9x=0 | | 6y=-6x-6 | | 88-3x=10x+32 | | x*11+4=y |